Integral inequalities of Gronwall type for piecewise continuous functions. (1997) - Bainov, Drumi D.; Hristova, Snezhana G.
Abstract : In this paper we generalize the integral inequality of Gronwall and study the continuous dependence of the solution of the initial value problem for nonlinear impulsive integro-differential equations of Volterra type on the initial conditions.